2019
DOI: 10.1111/ctr.13572
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in preformed panel‐reactive antibody levels and outcomes in patients undergoing heart transplantation

Abstract: Antibody-mediated immune processes play a key role in outcomes after heart transplantation. Panel-reactive antibodies (PRA) are circulating anti-human leukocyte antigen (HLA) antibodies directed against the donor major histocompatibility complex class I and II antigens that are expressed on allograft endothelial cells. 1,2 PRA levels of ≥10% indicate allosensitization, 3 a relevant risk factor for adverse outcomes. To date, only a small fraction of heart transplant recipients has relevant values of preformed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Higher PRA levels have been reported in Black compared with White populations, but sex imbalances between Black and White study participants may contribute to this perceived racial disparity (28,29). Elevated PRA are also associated with increased cardiovascular mortality in patients with ESKD (30). For example, a recent study observed that higher PRA was an independent predictor of cardiovascular and all-cause mortality among over 160,000 patients waitlisted for a kidney transplant (21).…”
Section: Discussionmentioning
confidence: 99%
“…Higher PRA levels have been reported in Black compared with White populations, but sex imbalances between Black and White study participants may contribute to this perceived racial disparity (28,29). Elevated PRA are also associated with increased cardiovascular mortality in patients with ESKD (30). For example, a recent study observed that higher PRA was an independent predictor of cardiovascular and all-cause mortality among over 160,000 patients waitlisted for a kidney transplant (21).…”
Section: Discussionmentioning
confidence: 99%